Wymiar gatunkowy zdania odrębnego i jego uzasadnienia na przykładzie orzeczeń Trybunału Konstytucyjnego w Polsce. Zarys problematyki - Buras-Marciniak, Anetta; Goźdź-Roszkowski, Stanisław (Języki specjalistyczne w komunikacji interkulturowej, 2020)
Surprisingly, there has been very little research into separate opinions in the legal linguistics literature. Very scarce attention has been paid to the linguistic and communicative aspects of how judges frame their disagreement. This chapter is one of the first attempts to examine the institution of votum separatum or separate opinion in the institutional context of Poland’s Constitutional Tribunal. It starts with an overview of the concept, its functions and the range of recipients. This is then followed by an examination of its form and structure. The study demonstrates how judges tend to employ highly formulaic expressions to signal their disagreement despite the absence of clear guidelines that would prescribe ways in which their stance should be communicated. In addition, the analysis shows that declaring votum separatum and providing its justification are two different acts, not only legally but also linguistically, especially in terms of their formulaicity. Finally, directions for future research are outlined.